Hydrogen kinetics limitation of an autotrophic sulphate reduction reactor (2012)
Sulphate-reducing bacteria (SRB) are microorganisms that can be used as removal agents in polluted water sources. The use of inorganic substrates in SRB systems could reduce the cost and simplify operation. However, the use of H2 as an energetic substrate and the production of H2S as a metabolic product could produce kinetic limitations. The aim of this study was to assess the extent to which the kinetics of a sulphate reduction bioreactor was limited by its gas transfer capacity. Reactor kinetics were monitored by total pressure kinetics without sulphate limitation. It was concluded that the bioreactor design should be based on transfer properties. The uptake rate of H2 reached a maximum of 10-4 M/min, equivalent to a sulphate reduction rate of 3.4 g·L-1·d-1. The hydrogen mass transfer rate required a kLa of 1.48 min-1 at 1.2·109 cells/L in order to avoid limitation by H2 bio-availability (1.23·10-9 L·min-1·cell-1), which is a relevant value for scaling-up purposes.